Global Prevalence of Tobacco Use in Adolescents and Its Adverse Oral Health Consequences - Nazir, Muhammad Ashraf (Open Access Maced J Med Sci, 2019)
BACKGROUND: Smoking is associated with various systemic conditions and contributes to a huge financial burden to economies around the world. AIM: The study aimed to evaluate global data about the prevalence of tobacco use among male and female adolescents and to discuss smoking-related oral complications. METHODS: The prevalence data of tobacco use among adolescents (13-15 years) was retrieved from the World Health Organization (Global Health Observatory). The World Bank’s statistics about gross national income (GNI) per capita were used to categorise low-income, lower-middle-income, upper-middle-income, and high-income countries. PubMed, Web of Science, Scopus, and Embase databases were searched to gather updated evidence about the adverse consequences of smoking on oral health among adolescents. RESULTS: The prevalence of tobacco use was 19.33%, and there were 23.29% of male and 15.35% female smoker adolescents in 133 countries (p < 0.001). The highest prevalence of tobacco use in male (24.76%) and female (19.4) adolescents was found in high-income countries. Significantly higher proportions of male adolescents were smokers than female counterparts in low-income, lower-middle-income, and upper-middle-income (p < 0.001). However, there were no statistically significant differences in tobacco use between male and female adolescents in high-income countries. Low-income countries had the lowest prevalence (14.95%) of tobacco use, while high-income countries had the highest prevalence estimates (22.08). Gingivitis (72.8%), gingival bleeding (51.2%), oral malodor or halitosis (39.6%) is common oral conditions among smoker adolescents. Smoking habit is significantly associated with dental caries, periodontal disease, hairy tongue, smoking-related melanosis, and hyperkeratosis among adolescents. CONCLUSION: There was a high prevalence of tobacco use among male and female adolescents around the globe. Available evidence suggests a strong association between smoking and compromised oral health among adolescents. Globally, measures should be taken to prevent and control the menace of tobacco use to reduce systemic and oral complications.